Hybrid Weakness Found in the Backcross Progeny of an Inter-Specific Cross of Oryza Sativa / O. Glumaepatula - Sobrizal Sobrizal; A. Yoshimura (PPIKSN-BATAN, 2009)
Hybrid breakdown expressed as sterility or weakness or both in F2 or later generations is considered to be a reproductive barrier between two distantly related taxa. Hybrid breakdown that showed poor growth habit with fertile seeds was found in the backcross progenies (BC4F2) which were derived from a cross between a cultivated rice Oryza sativa L. cv. Taichung 65 and a wild rice Oryza glumaepatula Steud (Acc. IRGC 105668) where Taichung 65 was used as a recurrent parent. Through segregation analysis of BC4F2 population, a novel gene for weakness was identified, and this gene was designated as hwf1 (hybrid weakness f-1). RFLP (Restriction Fragment Length Polymorphism) analysis was employed to determine the chromosomal location of hwf1 gene. The result revealed that hwf1 was located between G3006 and C933 RFLP markers, with map distances of 0.5 cM and 1.9 cM, respectively, and co-segregated with C708, C820, and R288 on the short arm of chromosome 4. Since both O. glumaepatula (Acc. IRGC 105668) and Taichung 65 that was used as parents showed normal growth habit, the weakness in this study was assumed to be controlled by a set of complementary recessive genes. One of the complementary genes is hwf1 from O. glumaepatula, and another gene should be from Taichung 65, because the genetic background of the BC4F2 populations that were used for analysis is Taichung 65. The gene from Taichung 65 has not been identified yet, therefore, it is necessary to conduct the experiment for finding out the complement of hwf1 gene in near future. Received: 20 November 2008; Revised: 15 May 2009; Accepted: 16 May 2009